Effect of Planting Time and Fertilizer Levels on Growth, Yield and Economics of Beta-Carotene Rich Bari Sweet Potato - Mondol, MRH; Prodhan, MZH; Rahman, MT; Islam, MM; Anwar, MB (Bangladesh Journal of Agricultural Research, 2023)
The experiment was conducted at the Tuber Crops Research Sub-Centre, Bangladesh Agricultural Research Institute (BARI), Bogura, Bangladesh during rabi 2020-2021 to investigate growth, yield and profitability of the beta-carotene rich of sweet potato var. BARI Mistialu-12 as influenced by the date of plantings and fertilizer doses. The experiment consisted four levels of planting dates viz. D1 = 30 October, D2 = 10 November, D3 = 20 November and D4 = 30 November along with four levels of fertilizers viz. F0 = control, F1= 60-55-80 kg of NPK, F2 = 80-75-100 kg of NPK and F3= 100-95-20 kg of NPK fertilizer per hectare. The experiment was laid out in a spilt plot design with three replications assigning planting dates in the main plots and fertilizer doses in the sub-plots. The results indicated that among all treatment combinations planting on 20 November with 100-95-120 kg of NPK fertilizer per hectare performed better in considering length of tubers (13.57 cm), breadth of tubers (41.95 cm), number of tubers per plant (9.93), yield (46.99 t ha-1), gross margin (Tk. 795,131/ha) and BCR (4.62). Marketable yield increased with the increasing of fertilizer doses. Bangladesh J. Agril. Res. 47(3): 343-353, September 2022